UNDERSTANDING RESEARCH AND RESEARCH COMPETENCE: SIGNIFICANCE AND BENEFITS (Universal International Scientific Journal, 2026)
This article examines the concepts of research and research competence, clarifyingtheir definitions, core characteristics, and professional significance. Drawing on a synthesis ofcontemporary scholarly literature, the paper analyzes how research is conceptualized as a systematic,rigorous, and purposeful process aimed at generating reliable knowledge and solving problems. Itfurther explores research competence as a multidimensional construct integrating knowledge,cognitive abilities, practical skills, motivation, and personal attributes necessary for effective researchpractice. The review identifies strong consensus across studies regarding the integrative nature ofresearch competence, despite variations in structural frameworks and component classifications.Additionally, the article highlights the educational and professional benefits of developing researchcompetence, including enhanced critical thinking, communication skills, motivation, academicachievement, and career readiness. Particular attention is given to its importance in graduate andpostgraduate education as a foundation for evidence-based practice and innovation. The findingsconfirm that fostering research competence is essential for quality education, professional excellence,and sustainable knowledge-based development.
Keywords: research; research competence; graduate education